Efek Terapi Menulis Ekspresif Terhadap Kecemasan Pasien Yang Menjalani Hemodialisa - Restuning Prihati, Dyah; Juanmita, Monica; Kustriyani, Menik (Universitas Duta Bangsa Surakarta, 2025)
Introduction: Psychological impact is the most felt impact by patients undergoing long-term hemodialysis. Anxiety about their incurable illness, fear of death, financial problems, difficulty in maintaining employment, impaired self-image, limited social activities because patients must undergo hemodialysis therapy. Expressive writing therapy is an action to express one's feelings and ideas about an event or painful emotional experience. Objectives: This study aims to analyze the level of anxiety of hemodialysis patients after being given expressive writing therapy intervention. Methods: This research method is quantitative quasi-experimental with one group pre-posttest design with 28 respondents. The anxiety level measurement tool uses the STAI (State-Trait Anxiety Inventory) Questionnaire. The statistical test used is the Wicolxon test. Results: The results showed that most respondents experienced mild anxiety levels of 16 respondents (57.1%), while after expressive writing therapy most had mild anxiety levels of 17 respondents (61%). The p-value of the Wilcoxon test 0.000 is less than ? (0.05), there is an effect on the level of anxiety of hemodialysis patients before and after expressive writing therapy is applied. Conclusions: The results of this study are used as evidence based in carrying out non-pharmacological interventions in dealing with anxiety in patients undergoing hemodialysis.